SECURING THE PATIENTS DATA ON IOT IN HEALTHCARE - M.SRUTHI; DR.RAJKUMAR.R (International Journal of Pharma and Bio Sciences, 2016)
Internet of things (IOT) in healthcare is the medical devices connected to the internet. In present there are many devices there are available such as ECG sensor, glucose sensor, Pulse sensor. Using this the vital signs can be monitored, controlled and actions can be taken during emergency situation. Thus IOT in healthcare can be used in an effective way for human community. Using the above health sensors they are connected to the internet for real time monitoring of the patient’s vital sign to take the action needed to the patient during an abnormal condition. So the works done so far using the IoT in healthcare and discuss the pros and cons of each system, and a secured system is proposed that use the IP address of the device and the GPS location information to encrypt the sensor data and the base station has a list of secured path in terms of ensures the low loss of packet or no loss of packet. Conclude what can be done further in healthcare using IOT.